2017
DOI: 10.17509/ijal.v7i1.6853
|View full text |Cite
|
Sign up to set email alerts
|

Child Comprehension of Adults’ Verbal Input: A Case of Bilingual Acquisition in Infancy

Abstract: Research concerning comprehension in early simultaneous bilingualism is still very limited. Thus, this study focuses on describing a bilingual infant's comprehension of adults' verbal input addressed to the child in an Indonesian-German language environment, and the child's understanding of translation equivalents (TEs). The child, who was exposed to Indonesian and German simultaneously from birth, was observed from age 0;9 to age 1;3 using a diary supplemented with weekly video recordings. A "one parent-one l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…As anyone with a YouTube account can upload their videos to YouTube, various languages are used, depending on the nationality and the choice of language preferred by the content creatures. This multilingual exposure can benefit bilingual children who learn new languages [28], [39], [51] either simultaneously or successively [16], [50]. In children learning English as their second language, the videos uploaded in English can be choices for their language exposure.…”
Section: Youtube and Bilingual Young Learnersmentioning
confidence: 99%
“…As anyone with a YouTube account can upload their videos to YouTube, various languages are used, depending on the nationality and the choice of language preferred by the content creatures. This multilingual exposure can benefit bilingual children who learn new languages [28], [39], [51] either simultaneously or successively [16], [50]. In children learning English as their second language, the videos uploaded in English can be choices for their language exposure.…”
Section: Youtube and Bilingual Young Learnersmentioning
confidence: 99%
“…Adults" verbal input plays an important role in children"s bilingual acquisition. Adnyani et al, (2017) added that input addressed to a child is focusing on the adult's speech input or an adult"s verbal input. de Houwer et al, (2006) pointed out that research in developmental bilingualism commonly tends to focus on language production.…”
Section: Adult's Verbal Input In Children's Bilingual Acquisitionmentioning
confidence: 99%
“…Current discussion on bilingualism practices through teachers' verbal input to children mostly highlighted about bilingualism practices at home by the parents (Adnyani et al, 2017), bilingualism practices and its influence on children's" L2 language development (Poulain & Brauer, 2018), and teacher"s bilingual verbal input in the classroom (Grøver et al, 2018). Adnyani et al, (2017); Grøver et al, (2018) found that the teacher"s verbal input has an important role in bilingualism practices toward children. As a result, future studies might investigate how adult"s verbal input might differ in their influence on child language development (Poulain & Brauer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of morphosyntactic separation was found by DeHouwer (1990), in comprehension by Adnyani, Beratha, & Suparwa (2017) and Nakamura (2010), in pragmatic by Nicoladis (1998) in phonology by Adnyani & Pastika(2016). This paper, is then trying to focus on the development of lexicon by a bilingual child exposed in Indonesian and German as well as looking at the translation equivalent which indicates that a bilingual child has the capacity to separate two different language systems.…”
Section: Introductionmentioning
confidence: 97%